Better survival of hybrid total knee arthroplasty compared to cemented arthroplasty: A report from the Norwegian Arthroplasty Register 1999–2012. (2nd November 2015) - Petursson, Gunnar; Fenstad, Anne Marie; Havelin, Leif Ivar; Gøthesen, Øystein; Lygre, Stein Håkon Låstad; Röhrl, Stephan M; Furnes, Ove
Abstract : Background and purpose — There have been few comparative studies on total knee replacement (TKR) with cemented tibia and uncemented femur (hybrid TKR). Previous studies have not shown any difference in revision rate between cemented and hybrid fixation, but these studies had few hybrid prostheses. We have evaluated the outcome of hybrid TKR based on data from the Norwegian Arthroplasty Register (NAR). Patients and methods — We compared 4, 585 hybrid TKRs to 20, 095 cemented TKRs with risk of revision for any cause as the primary endpoint. We included primary TKRs without patella resurfacing that were reported to the NAR during the years 1999–2012. To minimize the possible confounding effect of prosthesis brands, only brands that were used both as hybrids and cemented in more than 200 cases were included. Kaplan-Meier survival analysis and Cox regression analysis were done with adjustment for age, sex, and preoperative diagnosis. To include death as a competing risk, cumulative incidence function estimates were calculated. Results — Estimated survival at 11 years was 94.3% (95% CI: 93.9–94.7) in the cemented TKR group and 96.3% (CI: 95.3–97.3) in the hybrid TKR group. The adjusted Cox regression analysis showed a lower risk of revision in the hybrid group (relative risk = 0.58, CI: 0.48–0.72, p < 0.001). The hybrid group included 3 brands of prostheses: LCS classic, LCS complete, and Profix. Profix hybrid TKR had lower risk of revision than cemented TKR, but the LCS classic and LCS complete did not. Kaplan-Meier estimated survival at 11 years was 96.8% (CI: 95.6–98.0) in the hybrid Profix group and 95.2% (CI: 94.6–95.8) in the cemented Profix group. Mean operating time was 17 min longer in the cemented group. Interpretation — Survivorship of the hybrid TKR at 11 years was better than that for cemented TKR, or the same, depending on the brand of prosthesis. Hybrid fixation appears to be a safe and time-efficient alternative to cemented fixation in total knee replacement surgery.